Peran AKal dan Kebebasan Bertindak dalam Filsafat Ketuhanan Mu'tazilah - Analiansyah Analiansyah (Substantia: Jurnal Ilmu-Ilmu Ushuluddin, 2013)
Mu`tazilite is one of the Islamic theology schools. The school is quite  different from the other schools such as of the Sunnite and of the Shi`ite. Due to  its difference it is considered unique, mainly in the case of the role of intellect to  find the truth and the freedom human act. Consider to human freedom and the  power of intellect gifted by God, it is obliged to a Moslem to upgrade his intellect  in solving his problems of life, not solely dependent on the taqdir or God’s  determination. According to Mu`tazilte, through intellect, man is capable to  exploit natural sources for the human benefits as he likes rather than he depends  on the taqdir like a fatalistic point of view.